The relationship between trunk energy flow and collegiate softball hitting performance - Bordelon, N.; Wasserberger, K.; Downs Talmage, J.; Nebel, A. R.; Friesen, K.; Giordano, K.; Oliver, G. (ISBS Proceedings Archive (Michigan), 2023)
The purpose of this study was to determine the relationship between trunk energy flow and performance (exit velocity) during collegiate softball hitting. Nineteen collegiate softball athletes (age: 19.6 ± 1.0yrs) performed three maximal effort swings off a pitching machine. Kinematic data were collected using an electromagnetic tracking system. A segmental power analysis was performed to quantify peak rates of trunk energy flow (proximal inflow (IF) and distal outflow (OF) on front and back sides). Regression analyses determined exit velocity was best predicted by peak rate of distal trunk energy OF on the front side. On average, the model showed exit velocity increased by .9 mph for every 100 W increase in distal trunk energy OF on the front side while holding body mass constant.